Quantitative XRD characterisation and gas-phase photocatalytic activity testing for visible-light (indoor applications) of KRONOClean 7000 (R) - Tobaldi, D. M. (2017)
Carbon-modified commercial anatase (KRONOClean 7000 (R)) was quantitatively characterised with XRD for the first time - full phase composition (both crystalline and amorphous content) and microstructure. The material was found to be bimodal anatase, mostly similar to 4 nm diameter, but with a small amount of a larger fraction between similar to 12 and 15 nm. Absorption in the visible range was confirmed by UV-Vis analysis, whilst XPS showed that an aromatic carbon compound is at the origin of that absorption. Also, the photocatalytic activity of this commercial nano-TiO2 was assessed, monitoring the abatement of NOx using a white LED lamp, irradiating exclusively in the visible region. Experiments simulated an indoor environment, highlighting the potential of this nano-TiO2 for adoption as a standard for visible-light photocatalytic activity, i.e. applications for innovative interior eco-building materials.